2014
DOI: 10.1371/journal.pone.0107370
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Ocular Surface and Tear Inflammatory Mediators after Small-Incision Lenticule Extraction and Femtosecond Laser-Assisted Laser In Situ Keratomileusis

Abstract: PurposeTo characterize the early ocular-surface changes or tear inflammatory-mediators levels following small-incision lenticule extraction (ReLEx smile) and femtosecond laser-assisted laser in situ keratomileusis (FS-LASIK).MethodsForty-seven myopic subjects were recruited for this prospective study. Fifteen underwent ReLEx smile and thirty-two underwent FS-LASIK. Corneal fluorescein (FL) staining, tear break-up time (TBUT), Schirmer I test (SIT), ocular surface disease index (OSDI) and central corneal sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 42 publications
2
46
1
6
Order By: Relevance
“…Significant elevation of IL-6 has been found in ocular fluids derived from patients with refractory/chronic uveitis. Gao and colleagues25 reported elevated IL-6 following femtosecond laser-assisted laser in situ keratomileusis and refractive lenticule extraction. One study suggested that IL-6 was involved in promoting corneal wound healing 26.…”
Section: Discussionmentioning
confidence: 99%
“…Significant elevation of IL-6 has been found in ocular fluids derived from patients with refractory/chronic uveitis. Gao and colleagues25 reported elevated IL-6 following femtosecond laser-assisted laser in situ keratomileusis and refractive lenticule extraction. One study suggested that IL-6 was involved in promoting corneal wound healing 26.…”
Section: Discussionmentioning
confidence: 99%
“…39,81,82 Postoperative corneal sensitivity in small-incision lenticule extraction-treated eyes appears to be superior to that in femtosecond laser-assisted LASIK eyes as well. 83,84 The interrelation of corneal denervation and development of dry eye 85 has prompted investigation of dry-eye symptoms associated with small-incision lenticule extraction. Despite improved corneal sensation relative to LASIK, small-incision lenticule extraction does not appear to significantly decrease postoperative dry-eye symptoms.…”
Section: Corneal Nerve Integritymentioning
confidence: 99%
“…In previous studies, the safety, efficacy, and predictability of these treatments have been assessed by the change of visual function 8,9 and ocular anterior segment. 9,10 However, the change of ocular poster segment, especially choroid has rarely been evaluated following refractory surgery.…”
Section: Introductionmentioning
confidence: 99%